Is diet quality affected by nutritional knowledge and practices in individuals doing regular physical activity?: A cross-sectional study: ¿La calidad de la alimentación se afecta por conocimientos y prácticas nutricionales en individuos que realizan actividad física regular?: Un estudio transversal - Başpinar, Büşra (2023)
Background: This study aimed to determine the relationship between diet quality and nutrition knowledge (CN) and nutrition practices (NP) of people who perform physical activity (PA) regularly. Methods: Two hundred healthy individuals who attended the gym at least three times a week were studied. The quality of the diet is calculated using the Healthy Eating Index-2015 (HEI-2015). Linear regression models were used multiplex to assess associations between NC and PN scores and dietary variables. Results: Of the participants, 47.0% had poor NC and 48.0% had poor NP. It was determined that the PN scores were significantly associated with whole grain, seafood, and herbal protein and quality total diet (p < 0.05), while CN scores were not associated with the quality of the diet or its components (p > 0.05). A one-unit increase in CN score resulted in a 26.7% increase in snack consumption adjusted for age, sex, educational level, body mass index (BMI), smoking, alcohol consumption, and activity physical (PA)( p < 0.001). The evaluation of the PN score was related to the main meals (β = 0.065±0.013; 95% CI 0.04–0.09; p < 0.001), snack consumption (β = 0.029±0.014, 95% CI 0.01–0.06; p < 0.05), and total quality of diet (β = 0.894±0.329; 95% CI 0.24–1.54; p < 0.05). Additionally, about 17% of the variability in the PN score could be explained by CN scores. Conclusions: Elevated NC was associated with an increase in BW scores and indirectly with an increase in diet quality. In order to see the beneficial effects of PA on health, people must rely on a healthy diet, increasing your CN.